2016
DOI: 10.14202/vetworld.2016.869-874
|View full text |Cite
|
Sign up to set email alerts
|

Studies on clinical signs and biochemical alteration in pregnancy toxemic goats

Abstract: Aim:This study was planned to reveal the clinical signs and biochemical alterations in pregnancy toxemic goats.Materials and Methods:Blood samples were collected from 20 healthy pregnant and 45 pregnancy toxemic goats and analyzed biochemically.Results:The most significant clinical findings were observed in naturally affected goats with pregnancy toxemia included anorexia, recumbency, lethargy, opisthotonos, dropped head, periodic convulsion, sweetish fruity odor from breath, apparent blindness, bloat, grindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…During this period, fetal growth between 80 and 140 days of pregnancy corresponded to 92.6% of the total weight of the fetus (Castagnino et al, 2015). Although it is reported that pregnancy toxemia lowers albumin serum concentrations (Vasava et al, 2016), the animals in this study continued to be healthy without any signs of disease.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…During this period, fetal growth between 80 and 140 days of pregnancy corresponded to 92.6% of the total weight of the fetus (Castagnino et al, 2015). Although it is reported that pregnancy toxemia lowers albumin serum concentrations (Vasava et al, 2016), the animals in this study continued to be healthy without any signs of disease.…”
Section: Discussionmentioning
confidence: 62%
“…Serum urea concentrations are used to diagnose ketosis in goats, and pregnant goats with subclinical or clinical ketosis were reported to have higher serum concentrations of urea than goats without pregnancy ketosis (Vasava et al, 2016). Although we did not perform any biochemical tests for subclinical ketosis, clinical ketosis was not detected.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In fact, the impaired metabolism influences biological substances availability for lamb growth, with an increased risk of low birth weight, perinatal mortality and reduction of lambs’ performance [ 15 ]. A better knowledge of this disease would significantly improve the productivity [ 15 ] and the early diagnosis would allow a specific and effective management and medical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin and prolactin affect carbohydrate and lipid metabolism and can pose a risk of pregnancy toxemia [ 10 , 11 ], which occurs as a result of the negative energy balance due to the increased energy requirements of the fetus [ 12 , 13 ]. The hormonal effects in the late stages of pregnancy lead to decreased levels of glucose and increased fatty acid and ketone body concentrations in carbohydrate and fat metabolism [ 14 , 15 ]. The main indicators of sheep’s energy status are blood beta-hydroxybutyric acid (BHBA) and non-esterified fatty acid (NEFA) concentrations in the peripartum period [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%